Arabic Speaking Skills Development through the Ilqā' Al-Kalimāt Method: Pengembangan Keterampilan Berbicara Bahasa Arab melalui Metode Ilqā’ al-Kalimāt - Shadrina Irfandri, Suci; Mukhlishoh; Husnul Khatimah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2026)
Speaking proficiency is one of the essential skills in Arabic language learning that requires continuous practice and active language use. However, while previous studies have explored various approaches to developing Arabic speaking skills, limited attention has been given to the implementation of the Ilqā’ Al-Kalimāt method, particularly regarding its application process and the factors influencing its effectiveness. This study aims to examine the implementation of the Ilqā’ Al-Kalimāt method, identify its supporting and inhibiting factors, and analyze its contribution to the development of Mahārah Kalām among fourth-semester female students at the Cendekia Muslim Institute in Sukabumi.This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation and were analyzed systematically to obtain a comprehensive understanding of the implementation process and its outcomes.The findings reveal that the Ilqā’ Al-Kalimāt method is implemented through scheduled public speaking activities, vocabulary enrichment, regular speaking practice, and the participation of all female students on a rotating basis. Supporting factors include a conducive language environment, support from the Ilqā’ Department, and continuous practice. Inhibiting factors consist of limited vocabulary mastery, differences in language proficiency, and a lack of self-confidence among some students. The research findings indicate that female students view the Ilqā’ Al-Kalimāt method as contributing to the development of Arabic speaking skills through increased self-confidence, vocabulary enrichment, and opportunities for continuous speaking practice. Future research may explore the implementation of the Ilqā’ Al-Kalimāt method in different educational settings or examine its contribution to other Arabic language skills, such as listening, reading, and writing.